AI development requires regulatory oversight similar to what was established for nuclear technology. - Barthes (Isonomia, 2025)
AI development requires regulatory oversight similar to what was established for nuclear technology.
iso-id: iso:argument:DDDf1O8y; sha256: sha256:60c1de648d18652eabf89e41ef5734b6ebdafedbb9c5b0dfff9fd7838dcafdbe